Production of Femininity Discourse in Documentary Films (Critical Discourse Analysis of Our Mothers’ Land Films) - Pamungkas, Novi; Sokowati, Muria (Universitas Muhammadiyah Yogyakarta, 2022)
The documentary film is an audio-visual communication medium that tries to represent a social reality. The film entitled Our Mothers’ Land (Tanah Ibu Kami), one of the documentary films, is a form of social criticism of environmental issues and women. In fact, the environment as something that must be protected is everyone’s responsibility. Not only the responsibility of women or mothers. The diction choice of ‘mother’ in Our Mothers' Land strengthens the dominant ideology that femininity and nature are the responsibility of women. Meanwhile, on the other hand, being a destroyer of nature is the men’s job. Femininity as a fluid concept that is attached to women. In the end, the discourse of femininity is normalized by regimes in power. This study aims to reveal the gender ideology of the media and criticize the structure of reality against women, who are represented as the only entities with the obligation to protect nature. Using the critical discourse analysis method of Norman Fairclough's model, this study shows that the text, the relationship between texts, and their relationship to the social context in the film Our Mothers' Land will affect the construction of the discourse of femininity. From this study, I found that although the film Our Mothers' Land is a documentary film brings the spirit of women's freedom, this film is still trapped in the bias of representation of women's roles. This film constructs a discourse that women, femininity, and nature are inseparable things like something natural.